PENENTUAN PORTOFOLIO OPTIMAL DENGAN MENGGUNAKAN MODEL INDEKS TUNGGAL PADA SAHAM PEBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Permatasari, Monica (Jurnal Ilmiah Mahasiswa FEB, 2017)
Return and risk are two things that are related to investment. Investment activity in capital market has considerable risk and inevitable risk. Banking stock more prominent because every individual or company needs banking services so that the right choice as an investment choice to form a portfolio. The investment strategy to maximize return and minimize risk is by forming an optimal stock portfolio.This study aims to determine the optimal stock portfolio combination and proportion of banking companies listed in the Indonesia Stock Exchange using Single Index Model, along with theÂ  return and risk of the portfolio. The sample of this quantitative descriptive research was selected through purposive sampling technique, resulting in the stock of 24 banking companies during the period 2012-2015 together with secondary data.The results of this study show that there are five stocks that can form optimal portfolio using Single Index Model; they are BBCA with the fund proportion of 41.67%, SDRA with the fund proportion of 41.32%, BSIM with the fund proportion of 10.62%, BNBA with the fund proportion of 5.81%, and BBRI with the fund proportion of 0.58%. The expected return of the portfolio is higher than the risk, so the portfolio is worth to be consideration.Keywords: single index model, optimal portfolio, banking sector